Hiding of compressed bit stream into audio file to enhance the confidentiality and portability of a data transmission system - Bhattacharjee, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Data security is always an important aspect of any data transmission system. With the advancement of internet, various security threats and challenges are also becoming more powerful. However, among the various security challenges in any transmission system, confidentiality, portability, and data losses are most important concern. Therefore, to solve these issues, we have proposed a lossless fixed length coding based compression to reduce the file size and to increase portability of transmitted data. To enhance confidentiality and reduce data loss, the compressed bit stream is incorporated with in the audio file using a unique audio steganography. Efficiencies of the proposed technique are examined by experimented results and compared with other existing to show its effectiveness. Â© 2015 IEEE.